Study of E-Commerce Import Duty Exemption Tariff Based on Ministerial Regulation Number 112/PMK.04/2018 - Qotimah Nita Permata, Chusnul; Nada, Qotrun; Iqbal Baiquni, Muhammad (Universitas Negeri Semarang, 2019)
International Trade is now easy to access by all groups through online shops. Every International Trade activity is followed by customs obligations, one of which is the payment of import duties, export duties and taxes. Based on data released by kemenkeu.go.id, in 2015 state revenue from customs accounted for 10.2% of state revenue. This shows that the customs sector plays a role in state revenue, therefore it is necessary to carry out supervision. Indonesia as a developing country is still in the usual standards regarding the welfare of its people, there are even a small number of people who have not received what is called welfare. The author in this paper focuses on import duties, the authors argue that import duties can contribute a sizable amount of funds in order to improve people's welfare. The needs of today's society are increasing and varied. This need requires competition between foreign and domestic traders. In Ministerial Regulation Number 112/PMK.04/2018 article 13 paragraph (1) it is explained regarding exemption from import duty of a maximum of USD 75.00. This article clearly provides easy access for foreign products to enter the country. This also has an impact on the lack of public interest in local Indonesian products whose quality is not inferior to foreign products. The purpose of this writing is for the government to reduce import duty exemption rates again, so that it is not easy for foreign products to enter Indonesia.